(untitled) (Revista de Ciências Agroveterinárias, 2024)
The aim of the article was to evaluate the behavior and relationship of some spatial variability measures used in the agricultural context. The Degree of Spatial Dependence (SPD), the Spatial Dependence Index (SDI) and the Spatial Dependence Measure (SDM) were evaluated. The Spearman correlation was obtained between Sample size per hectare (n.ha-1), Coefficient of Variation [CV (%)], SDI (%), SDM (%), Range (m) and SPD (%), in each semivariogram model. The behaviors of SDI, SDM and SPD were compared, depending on the different semivariogram models. Exponential semivariogram generated higher spatial variability. The SDI and SDM measurements correlated with the CV only in the spherical semivariogram. The SPD correlated with the CV in the exponential and spherical semivariograms. SPD tends to generate fewer weak classifications of spatial variability, so it is suggested to consider moderate spatial variability from SPD values ​​of at least 45%.